The copper resistance operon copAB from Xanthomonas axonopodis pathovar citri: gene inactivation results in copper sensitivity - Teixeira, Elaine Cristina [UNESP]; de Oliveira, Julio Cezar Franco; Novo, Maria Teresa Marques; Bertolini, Maria Celia [UNESP] (Soc General Microbiology, 2008)
Xanthomonas axonopodis pv. citri (Xac) causes citrus canker and the completion of the Xac genome sequence has opened up the possibility of investigating basic cellular mechanisms at the genomic level. Copper compounds have been extensively used in agriculture to control plant diseases. The copA and copB genes, identified by annotation of the Xac genome, encode homologues of proteins involved in copper resistance. A gene expression assay by Northern blotting revealed that copA and copB are expressed as a unique transcript specifically induced by copper. Synthesis of the gene products was also induced by copper, reaching a maximum level at 4 h after addition of copper to the culture medium. CopA was a cytosolic protein and CopB was detected in the cytoplasmic membrane. The gene encoding CopA was disrupted by the insertion of a transposon, leading to mutant strains that were unable to grow in culture medium containing copper, even at the lowest CUSO4 concentration tested (0.25 mM), whereas the wild-type strain was able to grow in the presence of 1 mM copper. Cell suspensions of the wild-type and mutant strains in different copper concentrations were inoculated in lemon leaves to analyse their ability to induce citrus canker symptoms. Cells of mutant strains showed higher sensitivity than the wild-type strain in the presence of copper, i.e. they were not able to induce citrus canker symptoms at high copper concentrations and exhibited a more retarded growth in planta.